Feature Selection of OMIC Data by Ensemble Swarm Intelligence Based Approaches - Yao, Zhaomin; Zhu, Gancheng; Too, Jingwei; Duan, Meiyu; Wang, Zhiguo (Frontiers in Genetics, 2022)
OMIC datasets have high dimensions, and the connection among OMIC features is very complicated. It is difficult to establish linkages among these features and certain biological traits of significance. The proposed ensemble swarm intelligence-based approaches can identify key biomarkers and reduce feature dimension efficiently. It is an end-to-end method that only relies on the rules of the algorithm itself, without presets such as the number of filtering features. Additionally, this method achieves good classification accuracy without excessive consumption of computing resources.